Entrepreneurial and Information Systems Universities Applied to Master Students Management - Mustapha Bengrich,; Saïd Bribich,; Abderrahman Messaoud, (Iraqi Journal of Science, 2021)
Entrepreneurship, from a few years ago, is considered as a determining factor of the economic performances in the countries sending development. Its structural role and the dynamism it impels in all economies is no more established. For this reason, in this paper we proposed to use a methodology based on entrepreneurial and information systems for management master students in Ibn Zohr University Morocco. This methodology permit to facilitate to create the proper project in different disciplinary fields.Nowadays, all agents insist on the development of entrepreneurship as well as the creation of enterprises as a catalyst for global economic growth. In this spirit, the development of the culture of business creation among students is a key factor to emerge new generations of entrepreneurs driven by entrepreneurial passion for entrepreneurship and motivated by the culture of innovation. entrepreneurship mentality.Indeed, academic training is one of the determinants that significantly affects the spirit of entrepreneurship among students and recent graduates, and therefore on economic development in general. two questions arise, how do Ibn Zohr University master’s students perceive entrepreneurship, and does academic training and entrepreneurship awareness impact the intention and desirability of entrepreneurship in his students? To answer these questions, we developed a quantitative practical study based on a survey administered and collected from the young master’s students of Ibn Zohr University in Agadir. Thus, the results of this study show that the intention, desirability and feasibility of young students with respect to entrepreneurship are associated with personal, professional, cultural and contextual characteristics. And they differ between the different institutions of Ibn Zohr University.